Brocho-biliary fistula: A rare complication after ruptured liver abscess in a 3½ year old child - Kumar, Prawin (Lung India, 2015)
Bronchobiliary fistula (BBF) is a rare condition, defined by the presence of abnormal communication between biliary tract and bronchial tree. We describe a 3½-year-old child who developed BBF after rupture of liver abscess. She underwent exploratory laparotomy and peritoneal wash for ruptured liver abscess. Seven months later she presented with fever and cough with yellow-colored expectoration (bilioptysis). An abnormal communication between right branch of the hepatic duct and a branch of right main bronchus was identified. Child underwent right lateral thoracotomy and right lower lobectomy with surgical excision of sinus tract. On follow-up child was asymptomatic and doing well.